The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/ijc.34384
|View full text |Cite
|
Sign up to set email alerts
|

Performance of visual inspection of the cervix with acetic acid (VIA) for triage of HPV screen‐positive women: results from the ESTAMPA study

Abstract: Abbreviations: AI, artificial intelligence; ASC-US, atypical squamous cells of undetermined significance; CI, confidence interval; CIN, cervical intraepithelial neoplasia; cNPV, complement of the negative predictive value; ESTAMPA, EStudio multicéntrico de TAMizaje y triaje de cáncer de cuello uterino con pruebas del virus del PApiloma humano (Spanish acronym); GP, general practitioner; HPV, human papillomavirus; HSIL, high-grade squamous intraepithelial lesion; IARC,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 43 publications
(85 reference statements)
2
11
1
Order By: Relevance
“…When the cohort is stratified by age groups, we refer to the large European population-based screening studies, which offer a more comprehensive categorization of age groups in 5-year intervals . Our analysis revealed that triage with visual inspection exhibited a higher detection rate of CIN2+ cases among younger women, which was consistent with previous studies using visual inspection, genotyping, or cytology for HPV-positive triage . This phenomenon could be associated with the retreat of the squamocolumnar junction and the resulting challenges in visualizing endocervical disease in postmenopausal women .…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…When the cohort is stratified by age groups, we refer to the large European population-based screening studies, which offer a more comprehensive categorization of age groups in 5-year intervals . Our analysis revealed that triage with visual inspection exhibited a higher detection rate of CIN2+ cases among younger women, which was consistent with previous studies using visual inspection, genotyping, or cytology for HPV-positive triage . This phenomenon could be associated with the retreat of the squamocolumnar junction and the resulting challenges in visualizing endocervical disease in postmenopausal women .…”
Section: Discussionsupporting
confidence: 84%
“…Our results suggest that visual inspection may serve as an optional triage test among women whose results of the careHPV test were positive. In comparison with a multicenter, randomized clinical trial conducted in rural China in 2015, visual inspection demonstrated a lower positivity rate (18.3% vs 27.1%), which can be attributed to the subjective diagnosis by different physicians . Meanwhile, a greater detection rate of CIN2+ (2.8% vs 0.5%) and a significant reduction in the number of colposcopy referrals needed to identify 1 case of CIN2+ (4.2 vs 8.0) were observed in our study.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations